SAVI Approach Paper 15: Introduction to PERL: the SAVI Successor Progr amme - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engag ed Citizens Pillar’ (ECP) of a wider DFID-funded governance reform pro gramme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is ma naged by the same service provider, Palladium, and the same core manag ement team as SAVI, and many of the SAVI front line staff...